The Effects of Cellphone Use on the Academic Performance of Selected Grade 12 ABM Students in Bestlink College of the Philippines S.Y. 2018-2019 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Cellphones are considered as one of the needs and not as a want. It can distract teachers during the discussion and can cause disputes between teachers and students. The main concept of this study is to know if cellphones have a positive or negative impact on the students. The study observed that using cellphones help the students improve their academic performance. The researchers cited four variables such as study habits, behavior and attitude, and time management. A qualitative research method was used in this study. Using the descriptive research method, it focused on the assessment of Grade 12 Accountancy, Business and Management students. The researchers used four variables to determine the effects of using cellphones on academic performance such as Study habit, Behavior, Attitude and Time management. The data was collected by distributing survey questionnaires to the potential respondents using convenience sampling wherein the respondents were selected based on their availability to participate and join the study. The results of the study revealed that cellphone use affects the Academic performance of the grade 12 Accountancy, Business and management students in terms of the following variables: (1) Study Habit-shows that using Cellphones helped the students in their academic performance; (2) Behavior-shows that using cellphones helped the students to lessen their stress; (3) Attitude-shows that the use of cellphones made students comfortable; (4) Time Management-shows that students spend most of their time using cellphones rather than reading books. The results determined the Effects of cellphone use. This affects their academic performance. This study recommends that school administrators must provide a discussion about using cellphones and the study recommends the teachers ban cellphone use inside the classroom to avoid distractions on the discussion.
Keywords: cellphone, time management, behavior, attitude, distraction